Molecular Identification and Morphological Characterization of Ficus sp. (Moraceae) in Bogor Botanic Gardens - Hariri, Muhammad Rifqi; Peniwidiyanti, Peniwidiyanti; Irsyam, Arifin Surya Dwipa; Irwanto, Rina Ratnasih; Martiansyah, Irfan; Kusnadi, Kusnadi; Yuhaeni, Eni (Jurnal Biodjati, 2021)
Ficus spp. belongsÂ to the tribe Ficeae in the Moraceae family. Many members of this genus have been collected and grown in Bogor Botanic Gardens. There are 519 living collections of Ficus conserved since 1817, and 13 of them have not been identified until the species level. This research aimed to identify the Ficus sp. originated from Kaur Selatan (Bengkulu) using morphological and molecular approaches. Morphological characterization and herbarium specimen observation have been carried out to identify the Ficus sp. The molecular approach was conducted through DNA barcoding using ITS primer. The molecular identification using ITS sequence showed that Ficus sp. is Ficus crassiramea with 99.87% similarity to the sequence in NCBI. Morphological observation through herbarium specimen showed that there are 9 vegetative characters specific to Ficus crassiramea.